(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the optimization of fermentation processes for converting cattle manure into bio-fertilizer using complex microbial agents. The focus is on improving the efficiency and effectiveness of the fermentation process to enhance the nutrient content and quality of the resulting bio-fertilizer. Various parameters, including microbial composition, fermentation time, temperature, and aeration, are examined to determine their impact on the fermentation process. The results indicate that optimizing these parameters can significantly improve the quality of the bio-fertilizer produced, offering a sustainable and eco-friendly solution for managing cattle manure and enhancing soil fertility.